The Effect of Service Quality and Trust on Customer Satisfaction at Bank BNI Syari'ah Cirebon - Dede Ibrahim Maulana; Solihin; Muhammad Fikry Januar; Gilang Pratami (Journal of Applied Digital Business Management, 2025)
The main aim of this research is to analyze how far influence of service quality to consumer satisfaction and how far influence of consumer trust to consumer satisfaction at BNI Syari’ah Cirebon. This research represent the research assosiatif because meaning to find out the relation between two variable or more. With this research, hence will be able to be developing a theory which can function to explain, to forecasting, and controlling a symptom, and questioner measurement to variable formulated in statement item which refer at scale Likert, with the score qyration between 1-5. Variable in this research are variable of service quality (X1), consumer trust (X2), and consumer satisfaction (Y). data analyses by using SPSS 20.0 for windows. Result of research indicate that influence from service quality to consumer satisfaction is 10% and influence of consumer trust to consumer satisfaction is 3,5%, and influence of service quality and consumer trust to consumer satisfaction is 8,9%